Meniran (Phyllanthus niruri Linn) Extract Potential on Texel Sheep Feed Consumption, Body Weight Gain and Feed Conversion - Rara Irbah Fitriana Karimah; Sri Hidanah; Mohammad Anam Al-Arif; Kadek Rachmawati; Emy Koestanti Sabdoningrum; Suwarno (Jurnal Agro Veteriner, 2024)
Meniran contains phytochemical compounds that are efficacious for productivity. This research was conducted to determine the effectiveness of meniran extract on feed consumption, body weight gain and feed conversion ratio of Texel sheep. This research was conducted using Completely Randomized Design by divided 20 Texel sheeps into 4 treatments, each treatment consisted of 5 repetitions. The treatment groups consisted of : P0 (sheeps were given CMC-Na 0.5% solution), P1 (given meniran extracts at 5% concentration), P2 (given meniran extracts at 10% concentration) and P3 (given meniran extracts at 20% concentration). administration of treatment between groups using a syringe (20 ml) amount of 1ml/kgBB per oral. Data in the form of feed consumption, body weight gain and feed conversion ratio were then analyzed using ANOVA and continued with Duncan's test. The best result on body weight gain and feed conversion ratio by P1. This research show that meniran extracts had no effect on feed consumption but can increase body weight gain at 5% concentrations and decrease feed conversion ratio at 5% concentrations.